How the railroad will change life in Tuva? - Maady, Orlan B. (The New Research of Tuva, 2010)
Winner in the nomination "The art of the essay" contest "Tuva-2050: vision of the future"
Keywords: konkurs; Tuva-2050; foresight; youth; essay